NA’MATAK (ROSA CANINA L.) PLANTATSIYALARINI BARPO ETISH VA PARVARISHLASHNING TEXNOLOGIYASINI TAKOMILLASHTIRISH. - Xo’jaqulova Durdona Sadriddin qizi,; Tursunova Parizoda Panjiboy qizi, (TADQIQOTLAR, 2026)
This  graduation  qualification  work  studied  the  issues  of  improving  the technology of establishing and maintaining plantations of Rosa canina L. The study analyzed  the  biological  characteristics  of  the  plant,  agrotechnical  requirements, planting  schemes,  and  the  effects  of  irrigation  methods  on  productivity.  Particular attention was given to the adaptability of the plant to soil and climatic conditions, as well  as  the  possibility  of  obtaining  high-quality  medicinal  raw  materials. Recommendations  were  developed  for  the  efficient  organization  of  plantations, increasing  yield,  reducing  labor  costs,  and  applying  environmentally  sustainable technologies.  The  research  results  are  important  for  the  development  of  rosehip cultivation and for supplying high-quality raw materials to the pharmaceutical and food industries.